Prototype Development and Pre-Commercialization Strategies for Mobile Based Property Analytics - Omar, Mohd Faizal; Mahathir, Nurul Husna; Mohd Nawi, Mohd Nasrun; Zulhumadi, Faisal (International Journal of Interactive Mobile Technologies (iJIM), 2019)
No wadays, the government agencies are looking for strategies to strengthen their newly implemented policies for the nation building. The grassroots or the customer’s sentiments is very important to develop an inclusive policy with a mixed of bottom-up approach to incorporates the customer’s opinion. However, due to the unique political landscape and multiracial in Malaysia, current commercial off-the-shelf Social Analytics are irrelevant to capture the sentiments of multilingual characteristic for Malaysian native speakers. Current Social Analytic tool are lacking the quality of analysis for foreign languages such as Malay which limits the businesses to localize advertisement for a specific geographical area. Hence, this research is proposed to develop a real-time social media analytics tool with sentiment analysis specifically in Malaysian context in order to engage and analyze the customer reviews and opinions. The main purpose of this paper is to demonstrate our approach to utilize data from social media platforms such as Facebook and Twitter in gaining valuable insights to drive and improve marketing strategy in property industry. This research developed a tool namely Property Analytics to assess public sentiments on specific property project or services. The methodology and approach to enhance from lab scale to pre-commercialization activities are outlined in this paper. It is anticipates that our work is relevant to real world application, improve stakeholder’s decision making and people’s quality of life.